2017
DOI: 10.21873/cgp.20016
|View full text |Cite
|
Sign up to set email alerts
|

HTP Nutraceutical Screening for Histone Deacetylase Inhibitors and Effects of HDACis on Tumor-suppressing miRNAs by Trichostatin A and Grapeseed (Vitis vinifera) in HeLa cells

Abstract: Abstract. Background , with several miRNAs overlapping in the upward direction by both GSE and TSA (e.g. hsa-miR23b-5p, hsa-miR-27b-5p, hsa-miR-1180-3p, hsa-miR-6880-5p and hsa-mir-943

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The largely used corn, for example, in the form of corn oil induces a differential profile of the expression of tens of miRNAs related to carcinogenesis in the micro dissected liver of rats [136]. Moreover, the kaempferol, contained in grapes, green tea, and potatoes; the resveratrol of grapes, red wine, blueberries, and peanuts; the sinapinic acid in wine and vinegar; the diallyl disulfide of garlic; and the zerumbone of ginger have recently been considered as "natural HDAC inhibitors" [137] and show an in vitro anti-mitotic effect by regulating miRNAs involved in tumor suppression [138]. Hence, a further motivation to better study these dietary epigenetic regulators, some of them absent in MD, regarding their target specificity to gain potential anticancer dietary epi-adjuvants.…”
Section: American Foodsmentioning
confidence: 99%
“…The largely used corn, for example, in the form of corn oil induces a differential profile of the expression of tens of miRNAs related to carcinogenesis in the micro dissected liver of rats [136]. Moreover, the kaempferol, contained in grapes, green tea, and potatoes; the resveratrol of grapes, red wine, blueberries, and peanuts; the sinapinic acid in wine and vinegar; the diallyl disulfide of garlic; and the zerumbone of ginger have recently been considered as "natural HDAC inhibitors" [137] and show an in vitro anti-mitotic effect by regulating miRNAs involved in tumor suppression [138]. Hence, a further motivation to better study these dietary epigenetic regulators, some of them absent in MD, regarding their target specificity to gain potential anticancer dietary epi-adjuvants.…”
Section: American Foodsmentioning
confidence: 99%
“…However, Sannigrahi et al observed significantly decreased expression of hsa‐miR‐658 in an HPV‐positive HNC cohort and in TCGA tissue samples (Sannigrahi et al., 2018). Mazzio found that the overexpression of hsa‐miR‐23b‐5p could destroy some important oncogenes, including but not limited to NFkB , KRAS , MYC and AK2 (Mazzio & Soliman, 2017). Chang et al suggested that increased expression of mature hsa‐let‐7i‐5p could be predictive of improved breast cancer survival (Chang, Wang, Chapin, & Huang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A complex comprised of miRNAs and a protein known as RISC (RNA induced silencing complex) bind to the target mRNA and degrade it, causing gene silencing (103). miRNAs play crucial roles in the development, apoptosis, cell differentiation and proliferation under normal conditions (104). There is experimental evidence to indicate that a considerable number of miRNAs can play oncogenic or tumour-suppressive roles (105).…”
Section: Epigenetic Modifications In Human Cancermentioning
confidence: 99%